Generation of Aspergillus carbonarius mutants by Agrobacterium tumefaciens-mediated transformation method Obtenção de mutantes de Aspergillus carbonarius via transformação genética mediada por Agrobacterium tumefaciens - Maria Helena Pelegrinelli Fungaro; Luiz Rodrigo Morioka; Fernando Yuldi Ashikaga; Carla Beatriz Fier; Lígia Uno Lunardi (Semina: Ciências Biológicas e da Saúde, 2006)
Aspergillus carbonarius is a potent ochratoxin A producer, a mycotoxin that has nephrotoxic and carcinogenic effects. The knowledge of genes involved in biosynthesis of this toxin may be useful for the development of detection and control methods. The Agrobacterium tumefaciens-mediated transformation method has been demonstrated as a powerful tool to obtain insertional mutants for the characterization of new genes. The aim of this work was to adapt the A. tumefaciens-mediated transformation method for ITAL187 strain of A. carbonarius and to obtain transformants with alteration in ochratoxin A production. Conidia were transformed to hygromicin B resistance using AGL-1 strain of A. tumefaciens. The transformation frequency was 20,04 transformants per 105 target conidia. The transformation evidence was obtained by PCR and Southern Blot analysis. The last one showed us that  the hph gene integration was randomly in the genome fungi. Among 238 transformants, a total of 12 (5,042%) showed morphological variations. Three transformants (T44, T47 and T188) with consistently reduced and two transformants (T238 and T162) with increased ochratoxin A production were obtained. The identification of nocauted genes will contribute to ochratoxin A biosynthesis clarify. Aspergillus carbonarius é um potente produtor de ocratoxina A, uma toxina que apresenta efeitos nefrotóxico e carcinogênico. O conhecimento de genes envolvidos em sua biossíntese pode contribuir para o desenvolvimento de medidas de controle. O método de transformação genética mediado por Agrobacterium tumefaciens tem sido demonstrado como uma importante ferramenta para a obtenção de mutantes insercionais visando à caracterização de novos genes. O objetivo deste trabalho foi adequar o método de transformação genética via A. tumefaciens para a linhagem ITAL187 de A. carbonarius e obter mutantes alterados para a produção de ocratoxina A. Conídios foram transformados para resistência a higromicina B usando a linhagem AGL-1 de A. tumefaciens. A freqüência média de transformação foi de 20,04 transformantes por 105 conídios-alvo. A prova física da transformação foi obtida pela detecção do gene hph por PCR e Southern Blot. Esta última demonstrou que a integração do DNA exógeno ocorreu de forma aleatória no genoma fúngico. Dentre 238 transformantes, 12 (5,042%) mostraram variações morfológicas. Três mutantes (T44, T47 e T188) com significativa redução e dois mutantes (T238 e T162) com aumento da capacidade de produção de ocratoxina A foram obtidos. A identificação dos genes nocauteados contribuirá para a compreensão da biossíntese desta toxina.